“An Attempt to Understand the Relation Between the Cause and Effect in Homoeopathic Prescribing through a Clinical Case Report” (Advancements in Homeopathic Research, 2022)
Homeopathic physician deals with the present complaint which may be either the consequence of recent cause or may be the remote effect. The determining cause will be ‘the most significant points in the whole history of the chronic disease, to enable him to discover its fundamental cause, which is generally due to a chronic miasm’. The cause is the soil in which he is growing day by day since his first illness which reflects itself at the time of birth by different biological reaction of the individual with the trigger factors present at that time. Here the cause is neither the environment only nor the trigger factor only but is the miasmatic base, the soil which the baby nurtured. This is the ‘Causa Causarum’. Master Hahnemann also mentioned that the cause and effect are not always proportionately related. Here we are reporting cases where we have tried to understand the relation between cause and effect which helps in homoeopathic prescribing. A case of quadriplegia with the high serum cholesterol level in blood is presented as EBM (Evidence Based Medicine) with MRI report and lipid profile. Prescriptions were done in these cases with the help of causa causarum.
Keywords: causa causarum; quadriplegia; hyperlipidemia